A Conceptual Analysis of the Nature of Relationship Between Human Needs and Human Well-being in Social Work. (September 2022) - Moses, Balyejjusa Senkosi
The concept of human need and human well-being are commonly used in social work literature. However, their relationship remains unexplored. Although there is some literature on the relationship between human needs and human well-being in other fields, there is little literature explicitly analysing the nature of this relationship. Drawing on literature on both human needs and human well-being scholars from disciplines such as development studies, social policy, psychology, social work and so on, I argue that the relationship between human needs and human well-being is constitutive and instrumental-normative; and it is a two-fold relationship. Human needs are constitutive of human well-being, and human needs are preconditions for realising human well-being; they result into human well-being when adequately satisfied. I conclude by noting that this nature of relationship demonstrates that human needs are fundamental in promoting and realising human well-being. One cannot talk about human well-being without human needs. Therefore, social workers should focus on identifying and meeting clients' human needs in order to promote their well-being.